Acknowledging and understanding the contributions of nature to human sense of time - Correia, Ricardo A. (John Wiley & Sons Ltd., 2025)
There is growing evidence that interacting and connecting with nature are essential to maintain human health and well-being. The benefits of specific nature experiences and the cultural ecosystem services they provide are increasingly being recognized, but many others remain to be discovered and explored.
In this perspective piece, I argue that there is a need to better explore the pivotal role of nature experiences in shaping human time perception—our sense of time. Specifically, I outline the main elements of human time perception and the key factors that shape it, describe recent evidence showing that human time perception changes between urban and natural environments and discuss the potential societal gains from developing a better understanding of this relationship.
Human time perception is complex and involves at least three key dimensions related to temporal succession, temporal duration and temporal perspective. Time perception is shaped by various contextual factors, including the contents of the time period and the cognitive, emotional and bodily characteristics of the experiencer.
There is growing evidence that nature experiences can influence human sense of time by (i) extending human perception of temporal duration and (ii) shifting time perspectives. People who spend time in nature tend to overestimate the length of that experience and show a more positive outlook of the past, present and future, with less focus on a single-time perspective.
In the context of increasing time scarcity in modern urban societies with dire consequences for human health and well-being, I argue we need a better understanding of how nature experiences shape our sense of time and suggest how future research can provide actionable insights to help restore a healthier and more balanced relationship with time and nature.